Brucella modulates secretory trafficking via multiple type IV secretion effector proteins. - Sebenzile Myeni; Robert Child; Tony W Ng; John J Kupko; Tara D Wehrly; Stephen F Porcella; Leigh A Knodler; Jean Celli (PLoS Pathogens)
The intracellular pathogenic bacterium Brucella generates a replicative vacuole (rBCV) derived from the endoplasmic reticulum via subversion of the host cell secretory pathway. rBCV biogenesis requires the expression of the Type IV secretion system (T4SS) VirB, which is thought to translocate effector proteins that modulate membrane trafficking along the endocytic and secretory pathways. To date, only a few T4SS substrates have been identified, whose molecular functions remain unknown. Here, we used an in silico screen to identify putative T4SS effector candidate proteins using criteria such as limited homology in other bacterial genera, the presence of features similar to known VirB T4SS effectors, GC content and presence of eukaryotic-like motifs. Using β-lactamase and CyaA adenylate cyclase reporter assays, we identified eleven proteins translocated into host cells by Brucella, five in a VirB T4SS-dependent manner, namely BAB1_0678 (BspA), BAB1_0712 (BspB), BAB1_0847 (BspC), BAB1_1671 (BspE) and BAB1_1948 (BspF). A subset of the translocated proteins targeted secretory pathway compartments when ectopically expressed in HeLa cells, and the VirB effectors BspA, BspB and BspF inhibited protein secretion. Brucella infection also impaired host protein secretion in a process requiring BspA, BspB and BspF. Single or combined deletions of bspA, bspB and bspF affected Brucella ability to replicate in macrophages and persist in the liver of infected mice. Taken together, these findings demonstrate that Brucella modulates secretory trafficking via multiple T4SS effector proteins that likely act coordinately to promote Brucella pathogenesis.